Energy Security Scenario based on Renewable Resources: A Case Study of East Sumba, East Nusa Tenggara, Indonesia - Yulianto, Budi; Maarif, Syamsul; Wijaya, Chandra; Hardjomidjojo, Hartrisari (UI Scholars Hub, 2019)
This study aims to analyze the state of energy security in East Sumba, one of the four regencies dividing the Island of Sumba, East Nusa Tenggara Province, Indonesia. This region was chosen for this study as it is popularly known as the Iconic Island of Renewable Energy. Data was gathered by applying expert interview method and analytical hierarchy process. In sum, 30 source persons dealing with the energy security issue were interviewed: 11 government officials (G), 8 businessmen (B), 5scholars (A), 4 from the common society (C), and 2 from a financial institution. This study applied energy security index to assess energy security in East Sumba. The data was analyzed by using descriptive analysis and Eckenrode method, with energy security as a criterion. The study results show that the energy security index based on renewable resources in East Sumba is still relatively low (5.91). East Sumba is rich in natural sources of energy, such as sunlight, water, biomass, wind, and biogas. Factors such as poor affordability lead to a low energy security index in East Sumba, which is often a result of poverty. The natural vast hilly and grassland topography and the decentralized settlement of the people of East Sumba also lead to poor accessibility of energy. Moreover, the supporting infrastructure, such as roads, also causes a low index of energy security. The lack of an institutional model also discourages investors from investing in East Sumba. The electrification ratio in East Sumba is still low, reaching only 31%.